If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18=2(3x+6)x=1
We move all terms to the left:
18-(2(3x+6)x)=0
We calculate terms in parentheses: -(2(3x+6)x), so:We get rid of parentheses
2(3x+6)x
We multiply parentheses
6x^2+12x
Back to the equation:
-(6x^2+12x)
-6x^2-12x+18=0
a = -6; b = -12; c = +18;
Δ = b2-4ac
Δ = -122-4·(-6)·18
Δ = 576
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{576}=24$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-12)-24}{2*-6}=\frac{-12}{-12} =1 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-12)+24}{2*-6}=\frac{36}{-12} =-3 $
| -1+4x+23=135 | | 4^³x-⁵=1024 | | 9/4x=54 | | x/2=x/3+8 | | 2.5(2z+)=5(z+2.5) | | x²-10x+22=-2x-10 | | x²-10x+22=2x-10 | | 3−7*(3+4x)=−18 | | 2x-5/10=3 | | 4^+8=9.2^x | | 12/38,5=x/32,5 | | -10x2+31x+14=0 | | 9x+-5+3x+29=180 | | x+(1/3)x=1.3 | | 4b+6=2b+7 | | .65y=1.53 | | 3(1-2d)=10+d | | 3x+6(-x)=-3x | | 2x+28=10-4x | | 6p+5=5-6p | | x-80-0.6x=112 | | 7(x+8)=-7(x+2)+4x | | x-80-0.6x=113 | | 8x+10=5x-6 | | 50=14/xx100 | | -8-4(x-2)=8(5+2x) | | 10.8x-4.6=-21.97 | | 7x-3(4+x)=15 | | -3(3+2n)=2(n+3)+1 | | 2x(×+3)=360 | | 1/4(t+6)-10=-3t+2 | | 2x+28=3x+15 |